Daya Saing Sektor Pariwisata Dalam Meningkatkan Ekonomi Daerah Di Bali Dan D.I Yogyakarta Tahun 2017-2021 - Monika Presilia; Uswatun Khasanah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
One of the sectors with local revenue is tourism. The study will look at the tourist attractions in Bali and D.I. Yogyakarta. In this study, eight indicators were employed, and the World Tourism Organization (WTO) was used to examine them. According to the study's findings, each parameter is carefully analyzed. DIY displays a higher Human Tourism Indicator (HTI) score than Bali, and higher Bali indicators can also be found on the Infrastructure Development Indicator (IDI), Environment Indicator (EI), and Openness Indicator (OI). In terms of the Price Competitiveness Index (PCI), Technology Indicator (TAI), Human Resources Index (HRI), Openness Index (OI), and Social Development Index (SDI), Bali enjoys a competitive advantage. Keywords: Tourism Competitiveness, Tourism Index, Composite Index, Tourism Competitiveness Index.